Pengaruh Transformasi Digital dan Orientasi Pasar Terhadap Kinerja Usaha di Mediasi Keunggulan Bersaing Pada Usaha Laundry di Kecamatan Muara Bulian Kabupatan Batang Hari - Putri, Hilyati Ananda; Dahmiri, Dahmiri; Ihsan, Moh. (LPPM Institut Pendidikan Nusantara Global, 2025)
The purpose of this study is to determine and analyze the influence of digital transformation and market orientation on business performance in the mediation of competitive advantage in Laundry Business in Muara Bulian District, Batang Hari Regency. The analysis tool used is Partial Least Squares analysis. The results of the study show that digital transformation has a positive and significant effect on the business performance of business owners or employees of Laundry in Muara Bulian District, Batang Hari Regency, Market orientation has a positive and significant effect on the business performance of business owners or employees of Laundry in Muara Bulian District, Batang Hari Regency, Digital transformation has a positive and significant effect on the competitive advantage of business owners or employees of Laundry in Muara Bulian District, Batang Hari Regency, Market orientation has a positive and significant effect on the competitive advantage of business owners or employees of Laundry in Muara Bulian District, Batang Hari Regency, Competitive advantage has a positive and significant effect on the business performance of business owners or employees of Laundry in Muara Bulian District, Batang Hari Regency, Digital transformation has a positive and significant effect on performance through competitive advantage of business owners or employees of Laundry in Muara Bulian District, Batang Hari Regency and Market orientation has a positive and significant effect on performance through competitive advantage of business owners or employees of Laundry in Muara Bulian District, Batang Hari Regency.